Nós mesmos e os outros : etnomatemática e interculturalidade na Escola Indígena Paiter - Leite, Kécio Gonçalves (2014)
ABSTRACT: This doctorate thesis seeks to reflect mathematics education in the field of interculturality considering how empirical space the paiter indigenous schools. Ideas and assumptions set out in the discursive practices of indigenous teachers in the projection of teaching paiter mathematical knowledge and their intersections with the culture of Paiter people in schools of Terra Indígena Sete de Setembro, Rondônia, were observed, analyzed and interpreted in the field of interculturality. It demanded to investigate how the projection of a differentiated education in the villages that people can reframe traditional educational practices and promote revitalization of knowledge and practices of tradition, rather than a process of post-contact changes. For both, it was proposed to observe, listen and follow paiter teachers in their practices contextualized in daily of the schools, the villages and the university. Theoretically, the research was based on the perspective of ethnomathematics (D’AMBROSIO, DOMITE, GERDES, VERGANI), according to which, throughout the history of humanity, each people or human groups developed their own mathematical knowledge. Also guided by the concepts of interculturality and cultural hybridity (BHABHA, CANCLINI, HALL) addressed by Cultural Studies. Methodologically, the research is characterized as the qualitative interpretative approach. The case study was adopted as a method for the identification and registration of discourses, practices and ideas developed by indigenous teachers as well as for understanding the relationship of these ideas with the worldview, social organization and ethnicity of Paiter people. It was found that the discursive representation of paiter teachers in projecting the introduction of the mathematical knowledge of the people at school, besides seeking cultural diversity to which especially contribute the mathematical knowledge of the people, search dial position (opposition/differentiation) in relation to a mathematical curriculum of this school included in the village. This approach inevitably creates tensions related to issues of cultural identity, cultural decentralization and cultural hybridity because, while the enunciative process presupposes the existence of a tradition, it introduces a break in the performative present of cultural identification to elect new meanings and knowledge as needs of political present while practice of resistance. Thus, the empirical case of Paiter, is observed in the enunciative space represented by the discourse of teachers, simultaneously and of tensioned form, an appeal to the memories of a mathematical knowledge experienced or lived “by the elders”, and the recognition of the need for domain school mathematics as empowerment strategy in asymmetrical power relations with the surrounding society. Ensure a paiter cultural identity within that cultural hybridization process becomes a political concern of indigenous teachers, pointing to the introduction of mathematical knowledge of the people in school education as a strategy for strengthening identity. Theoretically, this fact indicates a possible link between ethnomathematics and ethnicity, to conceive etnomathematics not as assigned construct, but as claimed construct.